The Influence Of Product Innovation On Purchase Decisions At Ai-Cha Ice Cream & Tea In Pantai Indah Kapuk North Jakarta As A Beverage Franchise Product - Lia Natalie; Imam Ardiansyah (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
This study aims to determine the extent to which product innovation influences consumer purchasing decisions at Ai-CHA Ice Cream & Tea in Pantai Indah Kapuk, North Jakarta. Product innovation is considered important as it can affect consumer interest in choosing a product, especially amid the increasingly competitive beverage industry. The research method used is a quantitative approach. Data was collected through questionnaires distributed to 100 respondents using a simple random sampling technique. Data analysis included validity and reliability tests, multiple linear regression, t-test, F-test, and the coefficient of determination. The results show that partially, the dimensions of product quality and product variation have a significant effect on purchasing decisions, while product design does not. However, simultaneously, all three dimensions of product innovation together have a significant influence on consumer purchasing decisions. In conclusion, product innovation—particularly product quality and variation—plays an important role in encouraging purchases. Therefore, it is recommended that Ai-CHA Ice Cream & Tea Pantai Indah Kapuk continue to improve both quality and variety, and evaluate product design to better match current consumer preferences.